Genome-Wide DNA Methylation Analysis of Mammary Gland Tissues From Chinese Holstein Cows With Staphylococcus aureus Induced Mastitis - Wang, Mengqi; Liang, Yan; Ibeagha-Awemu, Eveline M.; Li, Mingxun; Zhang, Huimin; Chen, Zhi; Sun, Yujia; Karrow, Niel A.; Yang, Zhangping; Mao, Yongjiang (Frontiers in Genetics, 2020)
Staphylococcus aureus intramammary infection is one of the most common causes of chronic mastitis in dairy cows, whose development may be associated with epigenetic changes in the expression of important host defense genes. This study aimed to construct a genome-wide DNA methylation profile of the mammary gland of Chinese Holstein cows (n=3) following experimentally induced S. aureus mastitis, and to explore the potential gene regulatory mechanisms affected by DNA methylation during S. aureus mastitis. DNA was extracted from the S. aureus-positive (n=3) and S. aureus-negative (n=3) mammary gland quarters and subjected to methylation-dependent restriction-site associated DNA sequencing (Methyl-RAD Seq). Results showed that CmCGG/CmCWGG DNA methylation sites were unevenly distributed and concentrated on chromosomes 5, 11 and 19, and within intergenic regions and intron regions of genes. Compared with healthy control quarters, 9,181 significantly differentially methylated (DM) CmCGG sites and 1,790 DM CmCWGG sites were found in the S. aureus-positive quarters (P<0.05, |log2FC| >1). Furthermore, 363 CmCGG differently methylated genes (DMGs) and 301 CmCWGG DMGs (adjusted P<0.05, |log2FC| >1) were identified. Gene ontology and KEGG enrichment analysis indicated that CmCGG DMGs are involved in immune response pathways, while the CmCWGG DMGs were mainly enriched in gene ontology terms related to metabolism. The mRNAs of 526 differentially methylated CmCGG genes and 124 differentially methylated CmCWGG genes were also significantly differentially expressed (RNA-Seq data) in the same samples, herein denoted differentially methylated and expressed genes (DMEGs) (P<0.05). Functional enrichment analysis of DMEGs revealed roles related to cellular processes, especially the regulation of immune response to diseases. These results suggest potential regulatory roles for DNA methylation in bovine mammary gland processes during S. aureus mastitis and serves as a reference for future epigenetic regulation and mechanistic studies.